(untitled) (El-Wahat Journal for Research and Studies, 2021)
The reseach concerning the Arab heritage is an important issue, especially if it is related to a distinguished and a prominent scholar such as Al-Jhaiz, whose works and writings are characterized by excellence, skill, mastery and sophisticated intelligence. He is considered to be a man of knowledge and science, specifically when it comes to rhetorics. As he has a crucial role in giving it interest and granting it a distinguished place.What we aim at in this study is to search a case that we found features related to Al-Jahiz, it is the linguistic system and the appropriatenessof the case and their impact on the success of the communicative process at Al-Jahiz through his book Al-Bayan and Al-Tabin. key words - Appropriateness of the case -linguistic system – Communication- Connection- concerning -Al-Jahiz